Dual-mode narrowband organic photodetectors for self-aligned imaging in NIR-I and NIR-II - Yu Tang; Zhuangmiao Wang; Mingsheng Gao; Jiayin Han; Leiming Yuan; Furong Zhu (Nature Communications)
Abstract The ability to detect and image in the near-infrared (NIR) regions, specifically NIR-I (700–900 nm) and NIR-II (1000–1700 nm), is crucial for medical diagnostics and bioimaging due to their exceptional tissue penetration and absorption characteristics. Organic photodetectors (OPDs) present a promising solution for self-aligned imaging in these regions, due to their tunable optoelectronic properties and flexible fabrication processes. However, achieving high-performance dual-mode narrowband OPDs for NIR-I and NIR-II detection remains a significant challenge due to the inherently broadband nature of most organic semiconductor materials. In this study, we introduce a bias-switchable dual-mode narrowband OPD with a back-to-back stacked charge collection narrowing/photodiode-type double bulk heterojunction (BHJ) architecture. The dual-mode narrowband OPD exhibits excellent wavelength selectivity and enhanced imaging capabilities, facilitating self-aligned imaging in both NIR-I and NIR-II regions. Additionally, the double BHJ architecture provides design flexibility, allowing for the realization of dual-mode narrowband responses through various BHJ configurations.